2008
DOI: 10.1051/medsci/200824121083
|View full text |Cite
|
Sign up to set email alerts
|

Voie alternative d’activation de NF-κB et cancer

Abstract: Une vingtaine d'années après leur découverte, l'intérêt que suscitent les facteurs de transcription NF-κB (nuclear factor kB) émane de la multiplicité des réponses cellulaires auxquelles ces facteurs sont associés. Ils jouent en effet un rôle central dans la réponse inflammatoire, l'immunité innée et acquise, la balance survie/mort cellulaire, mais aussi la tumorigenèse [1][2][3][4][5]. Ainsi, une dérégulation de l'activité des facteurs NF-κB, via la production de formes anormales de NF-κB, ou un défaut de leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Several mechanisms of action for inhibition of NO production are described in the literature such as NF-κB, a transcription factor composed of a protein complex, located in cytoplasm and associated with the inhibitor IκB. 36,37 In response to various stimuli such as proinflammatory cytokines (IL-1β), LPS, or other forms of stress, IκB inhibitor is phosphorylated by the IKK kinase and then degraded. 36,38 This degradation promotes the activation of NF-κB and its release to join the nucleus where it attaches to inflammatory genes and activates the transcription of specific genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms of action for inhibition of NO production are described in the literature such as NF-κB, a transcription factor composed of a protein complex, located in cytoplasm and associated with the inhibitor IκB. 36,37 In response to various stimuli such as proinflammatory cytokines (IL-1β), LPS, or other forms of stress, IκB inhibitor is phosphorylated by the IKK kinase and then degraded. 36,38 This degradation promotes the activation of NF-κB and its release to join the nucleus where it attaches to inflammatory genes and activates the transcription of specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 In response to various stimuli such as proinflammatory cytokines (IL-1β), LPS, or other forms of stress, IκB inhibitor is phosphorylated by the IKK kinase and then degraded. 36,38 This degradation promotes the activation of NF-κB and its release to join the nucleus where it attaches to inflammatory genes and activates the transcription of specific genes. 39,40 This will lead to synthesis of cytokines and inflammatory mediators including TNF-α and NO.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with those findings, our results showed up-regulation of NF-κB-related proteins. Previous studies indicated that inactivation of NF-κB significantly inhibited tumor growth and development [ 40 ]. Our results also indicate that MG132 up-regulated IκB expression and down-regulated the protein levels of NF-κB and pNF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokine tumor necrosis factor α (TNFα), toll-like receptors (TLR), interleukine-1 (IL-1) and lipopolysaccharide (LPS) are some of the stimuli involved in its activation. The second one, the more recently described alternative NF-κB pathway, leads to the activation of RelB-containing dimers ( Figure 1 , right ) [ 7 , 12 , 13 ]. This pathway involves the NF-κB inducing kinase (NIK) that activates IKKα, thereby leading to the phosphorylation and proteasome-dependent processing of p100, resulting in the release of RelB/p50 and RelB/p52 dimers ( Figure 1 , right ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, accumulating evidence strongly suggest that an abnormal activity of RelB is involved in the development of both hematopoietic malignancies and solid cancers [ 13 ]. Constitutive activation of RelB/p50 dimers participates in the inhibition of DNA-damage-induced apoptosis in certain types of MALT lymphoma [ 46 ].…”
Section: Introductionmentioning
confidence: 99%